2018
DOI: 10.3892/ol.2018.8584
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin induced apoptosis of human oral cancer SAS cells through mitochondria and endoplasmic reticulum mediated signaling pathways

Abstract: Oral cancer is a cause of cancer-associated mortality worldwide and the treatment of oral cancer includes radiation, surgery and chemotherapy. Quercetin is a component from natural plant products and it has been demonstrated that quercetin is able to induce cytotoxic effects through induction of cell apoptosis in a number of human cancer cell lines. However, there is no available information to demonstrate that quercetin is able to induce apoptosis in human oral cancer cells. In the present study, the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Gao et al [54] reported that kaempferol induced extrinsic apoptosis through the death receptors/FADD/Caspase-8 pathway in human ovarian cancer A2780/CP70 cells. Quercetin treatment induced apoptosis in human oral cancer SAS cells by increasing the expression of Fas, Fas-Ligand, and caspase-8 [55]. Epiafzelechin was shown to downregulate anti-apoptotic protein Bcl-xl, of the Bcl-2 family as detected by western blot analysis (Figure 16).…”
Section: Discussionmentioning
confidence: 91%
“…Gao et al [54] reported that kaempferol induced extrinsic apoptosis through the death receptors/FADD/Caspase-8 pathway in human ovarian cancer A2780/CP70 cells. Quercetin treatment induced apoptosis in human oral cancer SAS cells by increasing the expression of Fas, Fas-Ligand, and caspase-8 [55]. Epiafzelechin was shown to downregulate anti-apoptotic protein Bcl-xl, of the Bcl-2 family as detected by western blot analysis (Figure 16).…”
Section: Discussionmentioning
confidence: 91%
“…MMPs inhibition occurs via the down-regulation of protein kinase C and the blocking of mitogen activated protein kinases (MAPK) and phosphatidylinositide-3 kinases (PI3K) signaling pathways and both cyclo-oxygenase-2 (COX-2) and NF-κB [93]. Moreover, quercetin affects the ratio of anti-/pro-apoptotic proteins in SAS cell lines, which may lead to the dysfunction of mitochondria followed by the release of cytochrome c (cyto c), apoptosis-inducing factors and endonuclease G from mitochondria, inducing cell-destruction by triggering apoptosis [94].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…The 10-40 µM quercetin concentration used in this study is commonly used for cancer cells under 24-h treatment conditions. Quercetin, a flavonoid found in many fruits, vegetables, and grains, has been shown to have an antitumor effect on OSCC cells via the induction of cell cycle arrest [29,40]. Quercetin treatment suppressed cell growth by inducing G2/M arrest and apoptosis in EGFR-overexpressing HSC-3 and TW206 oral cancer cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the antibacterial effects of quercetin against Actinobacillus actinomycetemcomitans (Aa) and Porphyromonas gingivalis (Pg), which are the major pathogens in PD [27,28]. Moreover, recently, studies have reported that quercetin inhibits the cell viability, migration, and invasion of OSCC cells [29][30][31][32]. However, its potential actions in OSCCs have been poorly explored.…”
Section: Introductionmentioning
confidence: 99%